Políticas públicas para a expansão do ensino superior no Brasil entre 2003-2014: reflexos na região Sudoeste do Paraná - Nunes, Hernani Flavio Pessatto (2018)
This work aims to conduct a documentary research, analyzing the numbers referring to the higher education national and regional district. In this way, we discuss the data that indicate the date of implementation of higher education institutions, the creation of respective courses, enrollment, tied students and graduates of the respective courses in the period 2003-2014. In order to do this, we have made a history of the formation of Brazilian higher education, the creation of the first institutions of higher education, the modernization of Brazilian post-1968 education and the work of international organizations in the sector, such as IBRD, International Bank for Reconstruction and Development, and the World Bank, attempting to mention the impositions of the Washington consensus that were influential in shaping economic and educational policies in Brazil in the following decades. During the construction of this history the discussions focused on education, we made relations with the economic and social policies of each period between 1930-2002. Based on the historical, we began the statistical discussion about the expansion of Brazilian higher education, based on the economic reformulation and from the institutionalized educational programs. Among them were: the Fund for Student Financing for Higher Education (FIES), the University for All Program (PROUNI) and the Federal University Restructuring and Expansion Program Support Program (REUNI). regions of the country, through state funding directed to the public and private sectors. Finally, we discussed the expansion of the teaching modality at the regional level, seeking to mention the data that indicates the date of implementation of the new educational institutions, the year of creation of the respective courses and, in municipal scope, we point out the numbers that indicate the number of enrollments, bound students, course finishes and the number of courses implemented. The problem that we investigated during the research was, the policies of expansion of education internalized the sector in the region, with the justification of a formation of higher education in a late form. We soon found that most educational institutions and courses were instituted dating to socioeconomic transformations from the 2000s. We also made clear that this research belongs to the research line "Education and Teaching of Geography" and to HEGEO - Group of Research in History and Epistemology of Geography.